(untitled) (Global Journal of Human-Social Science, 2019)
The objective of this article is to analyse the social and economic effectiveness of a mode of financing development based on foreign direct investment. To this end, a careful and endoscopic observation of the recent economic literature has enabled us to see that FDI, through the mechanisms of the fiscal competition it generates between States, could in one way or another affect the socio-economic, tax and even redistributive variables of a host country. Thus, using the VAR modelling in this article, we realized that these foreign capital flows have a mixed effect on the quality of income redistribution in Cameroon.